State of Vegetative Homeostasis in Children with Anthracycline-Induced Cardiomyopathy - T.V. Shatynska; O.B. Synoverska; S.B. Shkandriy (Zaslavsky O.Yu., 2014)
The paper presents the results of investigation of the autonomic nervous system in children with acute lymphoblastic leukemia, in whom as a result of protocol chemotherapy with anthracycline antibiotics application, toxic anthracycline-induced cardiomyopathy developed. Distribution of research groups had been carried out according to age status and cumulative dose of doxorubicin. Investigation of the autonomic nervous system included evaluation of baseline autonomic tone, autonomic reactivity and vegetative status, which has been carried out in the end of the first phase за I, II and mM protocols of polychemotherapy. Evaluation of vegetative status of children was performed by analysis of heart rate variability. Evaluation of the baseline autonomic tone showed imbalance between the systems of regulation and the predominance of sympathetic influence on the cardiovascular system activity during the whole period of polychemotherapy. It is found that in the majority of surveyed children there was observed reduced autonomic reactivity with predominance of paradoxical response. There has been defined a clear stress in regulatory systems due to increasing stress index during the whole period of chemotherapy. In addition, it was found that a number of heart rate variability indices in children is closely correlated with the duration of polychemotherapy and the cumulative dose of anthracycline antibiotics.